Application and Potential of Drone Technology in Oil Palm Plantation: Potential and Limitations. (1st September 2022) - Khuzaimah, Zailani; Nawi, Nazmi Mat; Adam, Siti Nooradzah; Kalantar, Bahareh; Emeka, Okoli Jude; Ueda, Naonori
Abstract : Oil palm has become one of the largest plantation industries in Malaysia, but the constraints in terms of manpower and time to monitor the development of this industry have caused many losses in terms of time and expense of oil palm plantation management. The introduction to the use of drone technology will help oil palm industry operators increase the effectiveness in the management of oil palm cultivation and production. In addition, knowledge gaps on drone technology were identified, and suggestions for further improvement could be implemented. Therefore, this study reviews the application and potential of drone technology in oil palm plantation, and the limitation and potential of the methods will be discussed.